Ecotheological Construction in Islamic Education: A Study of the Ethics of Environmental Conservation and Deforestation - Achmadin, Balya Ziaulhaq; Barizi, Ahmad; Roibin, Roibin; Haris, Abd.; Mukhsin, Akhmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study examines the construction of Islamic eco-theological values in the Islamic education system, with a particular focus on the ethics of environmental conservation learning and responses to deforestation issues. This study is motivated by the urgency of the global ecological crisis and the strategic potential of religious education in shaping sustainable environmental awareness. Using a qualitative approach with a case study design at Islamic boarding schools in East Java, this study collected data through participatory observation of the learning process, in-depth interviews with teachers, ustaz, and santri, as well as analysis of curriculum documents and syllabi. The findings reveal that the construction of Islamic eco-theological values is built through four integrated approaches. First, the integration of theological concepts such as khalifah, amanah, and mizan (balance) into formal subjects. Second, the implementation of transformative learning ethics that link theory with direct field practice, such as reforestation and waste management programs. Third, the internalization of values through the living Qur'an approach, where students are invited to reflect on kauniyah verses related to environmental damage.  Fourth, the ecological exemplarity (uswah hasanah) demonstrated by pesantren caregivers in their daily lives. This study found that effective learning ethics emphasize a humanistic-ecological approach, where the issue of deforestation is not only studied as a technical problem, but as a form of fasad fi al-ardh (damage to the earth) that contradicts the principles of maqashid syariah. The main supporting factor lies in the consistency between the values taught and daily practices, while the main challenge is the lack of structured teaching materials on Islamic ecotheology. This study concludes that Islamic education has strategic potential in shaping comprehensive ecological awareness when ecotheological values are constructed through a holistic approach that combines theological, ethical, and practical dimensions. The findings of this study recommend the development of a systematic Islamic eco-theology learning model that can be implemented in various Islamic educational institutions.